Marvel Comics in the 1970s : The World inside Your Head - Borenstein, Eliot, 1966- (Book collections on Project MUSE., 2023)
"With the rise of new creators who emphasized their own individual voices while also focusing on their characters' inner lives, Marvel Comics in the 1970s laid the groundwork for the next decade's breakthroughs, expanding our sense of what the comics medium can do and what the superhero genre makes possible"--